Factors Associated with Poor Clinical Outcomes in Patients with Post- Cataract Surgery Endophthalmitis: A systematic review: Poster Presentation - Observational Study - General practitioner - Amran, Rahmah; Zukhri, Sp.M, dr. Dicky Stevano (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Postoperative Endophthalmitis has remained one of the rare yet most devastating complications of cataract surgery. The previous study mentioned that 15-30% of POE patients have an unfavorable outcome on visual acuity of less than 20/200 and may even result in the loss of the eye. Thus, this study aims to review and summarize prognostic factors that can affect the final outcome of postoperative endophthalmitis from cataract surgery. Methods : We systematically searched with PRISMA 2020 across 5 databases (PubMed, Scopus, SAGE, Embase, and Cochrane) with the search term “(prognosis OR prognostic factor) AND postoperative endophthalmitis) AND (cataract surgery)”, as well as reference screening for any additional relevant studies. The risk of bias from included studies will be assessed using Newcastle-Ottawa Quality Assessment Scale. Results : Out of 314 studies, we decided to only include 13 studies that match our inclusion and exclusion criteria. All of the studies are cohort studies with a total of 753 patients affecting 753 eyes and most of them are coming from Asian countries. Both diagnosis and intervention given are based on Endophthalmitis Vitrectomy Study (EVS) result. Conclusion : Prognostic factors for post-cataract surgery endophthalmitis are corneal involvement, microbiological investigation result, intervention timing, treatment modality, comorbidities, and other complications